2018
DOI: 10.1080/0361073x.2017.1398810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-cost resistance training on lower-limb strength and balance in institutionalized seniors

Abstract: The findings support the feasibility and efficacy of a simple and inexpensive resistance training program to improve lower-limb muscle strength and dynamic balance among the institutionalized older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 42 publications
4
21
0
10
Order By: Relevance
“…The result of the study is consistent with the study of Vechin et al (2015) The result of the study is consistent with the study done by Motalebi, Cheong, Iranagh, and Mohammadi (2018) that there is an improvement of lower limb strength and dynamic balance among the institutional elderly participants after receiving foot exercise training. Another study which supports the findings was conducted by Maritz, Patel, Varughese, and Yecco (2013).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The result of the study is consistent with the study of Vechin et al (2015) The result of the study is consistent with the study done by Motalebi, Cheong, Iranagh, and Mohammadi (2018) that there is an improvement of lower limb strength and dynamic balance among the institutional elderly participants after receiving foot exercise training. Another study which supports the findings was conducted by Maritz, Patel, Varughese, and Yecco (2013).…”
Section: Resultssupporting
confidence: 90%
“…The result supports the findings as shown in table 4 which shows that those participants who were engaged in foot exercise have stronger lower limb and better balance function. The result of this study is consistent with the study done by Motalebi, Cheong, Iranagh, and Mohammadi (2018) which found out that there is a significant improvement in lower-limb muscle strength and balance among the elderly after intervention of twelve weeks of progressive elastic resistance training on lower limb. Another study which support the findings was done by Josephson and Williams (2017) which found out that intervention group with strength training program significantly improved in balance control with a mean of 3.33 point when compared to the control group with mean of .83 point.…”
Section: Difference In Lower Limb Strength and Balance Between Baselisupporting
confidence: 92%
“…Além disso, a carga foi um elástico e não caneleiras, como no presente estudo. 23 As intervenções de exercícios parecem ter um papel no aumento da força muscular e na melhoria do desempenho físico, embora não pareçam aumentar consistentemente a massa muscular, em indivíduos idosos frágeis, sedentários e residentes da comunidade. 14 Com base nos estudos realizados por Faria et al 24 o fortalecimento muscular foi efetivo em melhorar a FM, a mobilidade funcional e o equilíbrio de indivíduos idosos.…”
Section: Discussionunclassified
“…That is why to develop a healthy community, the healthy lifestyle should be promoted among its members; therefore, the health-related objectives such as encouragement of healthy behaviors and providing healthy social and physical environment should be achieved (23). As aging increases throughout the world (24)(25)(26), resolving the needs and challenges of the elderly is one of the social necessities (27). This highlights the necessity of paying attention to the elderly with stroke.…”
Section: Introductionmentioning
confidence: 99%